The power of Gamifographics learning - Tan, Xiao Wei; Yip, Wen Qi; Md Yunus, Melor (Academica Press Solutions, 2023)
YouTube, Instagram, games, animations and infographics are some visual media outlets that Malaysian learners opt for in the 21st-century classroom. Nonetheless, pupils in primary school nowadays are not able to retain English vocabulary due to teachers' chalk-and-talk method in teaching vocabulary. Hence, this research aims to innovate the use of ‘Gamifographics’ with primary school pupils in learning vocabulary as it is one of the most appealing means to better understand and retain vocabulary. To support the research, four theories are applied which are Cognitivism learning theory, Bloom’s Taxonomy, Gamified-Learning Theory and Self-determination theory. A Design and Development Research (DDR) approach, ADDIE Model was employed in the study to innovate the use of ‘Gamifographics’ with primary school Year 4 pupils in an urban and a suburban school in learning vocabulary. Generally, findings revealed that "Gamifographics" has gained positive perceptions in learning vocabulary as they are visually attractive, easy to understand and remember as well as keep the readers' interest in continuing reading. In addition, "Gamifographics" promotes learning motivation, improves learning engagement and ultimately leads to a positive learning outcome. Thus, it is suggested that utilising of "Gamifographics" in learning vocabulary among primary English learners should be regarded.